Active force control applied to a rigid robot arm - Mailah, Musa; Hewit, J. R.; Meeran, Sheik (Faculty of Mechanical Engineering, 1996)
The paper presents the implementation of Active Force Control (AFC) strategy to control a rigid robot arm. The robustness and effectiveness of AFC as 'disturbance rejector' is demonstrated through a simulation study using MATLAB(R) and SIMULINK(r)* softare packages. The work is carried out on a rigid two link disturbances. The results are directly compared to an equivalent system which employs the conventional model-based Proportional-Derivative (PD) control method.